INHIBITING FACTORS IN LEARNING PHYSICAL EDUCATION IN STUDENTS OF SALAF BOARDING SCHOOL-BASED SCHOOLS - Ilmi, Dewi; Yono , Topo; Nurhasyim, M Saleh (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Abstract. The purpose of this study was to determine the factors that inhibit physical education learning in female students of SMK IBU Pakusari. This study was conducted at SMK IBU Pakusari, Pakusari District, Jember Regency. This study used a qualitative descriptive research type with data collection techniques using observation, interviews, and documentation. Research This descriptive study aims to investigate a circumstances, conditions or other things described in form report research. In this research researcher try describe the actual event based on the data and information obtained. The focus of the data taken in This research is factors that become inhibitor students in learning education physical. The purpose of this study is to find in-depth information in the form of data, descriptions, and knowledge regarding factors that hinder female students from participating in educational learning. The results of this study indicate that the factors that inhibit students in participating in physical education learning at SMK IBU include (1) internal factors: anxiety due to fear of injury, lack of self-confidence; (2) internal factors: poor facilities and infrastructure. For this reason, efforts are needed to develop learning methods or models that can reduce obstacles in learning.